The effect of implant number and position on the stress behavior of mandibular implant retained overdentures: A three-dimensional finite element analysis - Topkaya, Tolga; Solmaz, Murat Yavuz (Elsevier Sci Ltd, 2015)
The present study evaluated the effects of ball anchor abutment attached to implants with a 430 mm diameter and 11 mm insert length on stress distribution in a patient without any remaining teeth in the lower jaw. In the study, the stress analysis was performed for five different configurations (2 with 4 implant-supported and 3 with 2 implant-supported) and three different loading types using ANSYS Workbench software. The stresses measured in the 4 implant-supported models were lower compared to the stresses measured in the 2 implant-supported models. The stresses on the implants intensified on the cervical region of the implants. When the effects of the loading sites on the stress were examined, the loading on the first molar tooth produced the highest stresses on the implants. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dental implant; Removable overdenture; Finite element method